257 WHERE AND WHY HAVE ALL THE NURSES GONE? PERCEPTIONS OF NURSING STUDENTS IN KAMPALA, UGANDA. Issue 1 (1st January 2007) - Nguyen, L.; Ropers, S.
Abstract : Background: Worldwide, countries from Uganda to the United States are reporting severe nursing shortages. While the United States has 773 nurses to 100, 000 population, Uganda has a corresponding 6 nurses to 100, 000 population. Contributing to this health crisis is the ever-increasing rate of "brain drain, " in which African health professionals are emigrating to work in these more developed countries. An added problem is the rural versus urban distribution of health workers remaining in the country. This is the first study to focus on the perceptions of students still in their nursing education about their views on emigration and practice location. A better understanding of these perceptions could lead to changes in current practices and policies that would encourage the retention of future nurses. Methods: Anonymous, close-ended (Likert 5-point scale) questionnaires were distributed to all nursing students at the Makerere Medical School and Aga Khan University in Kampala, Uganda, during July 2006 using convenience sampling methods. Results: Sense of profession and loyalty to country distinguished students wanting to work in rural/public/, or African countries compared with those wanting to work in urban/private /UK/ or US ( p < .05). Those who have lived in rural areas were less likely to report wanting to emigrate to the United Kingdom. Conversely, those wanting to move to the United Kingdom thought that rural areas were unsafe and would not want to work in a rural setting. Students with an interest to work in urban areas or private practice said that they would emigrate for financial reasons and country stability, whereas students wanting to work in rural areas or public practice were less likely to want to emigrate overall ( p < .05). Additionally, a mother's educational level influenced emigration choice to the United Kingdom or United States but not to other African countries ( p < .05). Conclusion: Policy implications based on this study include the following: (1) more vigorous recruitment of nursing students from rural areas could lead to a more stable workforce in Uganda; (2) interviews, recommendations, and personal goal statements could be evaluated in the admission process to favor those candidates likely to express a commitment to rural practice or continued service to Uganda; (3) Ministry of Health acknowledgment of the role of country stability and health workforce remuneration in attracting and retaining nurses could lead to policy choices that accomplish those goals.